SERVICE AND PATIENTS PARTICIPATION ON SATISFACTION AND TRUST - Bambang Suroto; Hadiyati Hadiyati; Juanim Juanim (TRIKONOMIKA, 2020)
In addition to being provided by private service providers, satisfactory services are also important for a government-owned service provider to build customer trust. The purpose of this research is to identify whether satisfaction from service and participation affects customer trust in government-owned hospitals. The research was conducted at RSUD Arifin Ahmad Pekanbaru using a survey method on a sample of outpatient service recipients. The sample consisted of 100 people who were selected using accidental sampling. The data were collected using a questionnaire and the analysis tools, namely SEM and WarpPLS software. The results showed that service and patient participation in services has a significant effect on patient satisfaction. In addition, patient satisfaction also has a significant effect on patient trust in government-owned hospitals.